Effect of Rovabio® Max AP on Performance, Energy and Nitrogen Digestibility of Diets High in Distillers Dried Grains with Solubles (DDGS) in Broilers - Min, Y.N.; Liu, F.Z.; Karimi, A.; Coto, C.; Lu, C.; Yan, F.; Waldroup , P.W. (International Journal of Poultry Science, 2011)
This experiment was conducted to evaluate the effect of a commercial carbohydrase preparation (Rovabio® Max AP) on protein and energy utilization of diets with 0 or 30% DDGS. One hundred and ninety two, 18-day old male broiler chicks of a commercial strain (Cobb 500) were randomly distributed among six treatments in a 2 x 3 factorial arrangement. Each treatment was replicated four times, with six chicks per replicate. Treatments included two basal diets containing 0 or 30% of DDGS; each supplemented with or without an enzyme preparation fed at the level recommended by the manufacturer (1X), two (2X) and four times (4X) the recommended level. After a five-day adaptation period, excreta samples were collected for determination of AME and N retention (NR). Body weight, feed intake, feed conversion, fecal gross energy (GE) and N, AME, AMEn, GE digestibility and NR were determined. The results showed that weight gain, feed intake, feed conversion ratio and mortality rate were not significantly affected by level of DDGS or enzyme inclusion in the diet, or their interactions. Excreta N and GE were significantly increased by inclusion of 30% of DDGS in the basal diet. While AME and AMEn values were not affected by the addition of high level of DDGS in the diet, GE digestibility and NR were significantly affected. Supplementation of either basal diet with different levels of enzyme had no significant effects on excreta N content or AME, GE digestibility, or NR values. Moreover, the interaction between different levels of DDGS and enzyme levels on performance or nutrient utilization parameters were not significant. These data indicate that the addition of the enzyme preparation used in this trial was not effective in improving nutrient utilization of corn-soybean meal diets with or without DDGS.